2013
DOI: 10.1097/ta.0b013e31827c5f66
|View full text |Cite
|
Sign up to set email alerts
|

The effects of location and low-molecular-weight heparin administration on deep vein thrombosis outcomes in trauma patients

Abstract: Therapeutic study, level IV; epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Two recent studies indicate that it is. Lee et al 25 showed that above-knee and below-knee DVTs had the same risk of PE (4.7% and 3.3%, respectively, p = 0.59). Olson et al 26 found that below-knee DVT had a higher rate of PE than did above-knee DVT (6.1% and 1.1%, respectively, p = 0.1) and that below-knee DVT propagated to either aboveknee DVT or PE in 12.9%.…”
Section: Discussionmentioning
confidence: 96%
“…Two recent studies indicate that it is. Lee et al 25 showed that above-knee and below-knee DVTs had the same risk of PE (4.7% and 3.3%, respectively, p = 0.59). Olson et al 26 found that below-knee DVT had a higher rate of PE than did above-knee DVT (6.1% and 1.1%, respectively, p = 0.1) and that below-knee DVT propagated to either aboveknee DVT or PE in 12.9%.…”
Section: Discussionmentioning
confidence: 96%
“…Some authors suggested the risk of proximal DVT was related to the fracture sites that were higher in fractures more proximal to the hip [ 10 , 22 , 23 ]. Anyhow, we did not ignore the role of distal DV, and in some study, it demonstrated to present a similar risk of pulmonary embolism as proximal DVT [ 24 ]. We also observed the relatively few incident DVTs in the bilateral (rate, 5.1%) or even only in uninjured extremity (rate, 2.0%), which was consistent with the previous finding [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is lower than in general orthopaedic surgery where the rate of DVT is reported as 40–60 % [ 23 ], but similar to the incidence of DVT following knee arthroscopy which has been reported as 0.6 % when diagnosed clinically and up to 17.9 % when using radiography [ 31 , 60 ]. The consequences of asymptomatic below knee DVT and the importance of its prevention and treatment remains controversial and a systematic review of the treatment of below knee DVT’s concluded there was insufficient evidence to recommend treatment over mere surveillance [ 8 , 19 , 29 , 34 , 43 , 45 , 58 , 61 , 74 ].…”
Section: Discussionmentioning
confidence: 99%